2003
DOI: 10.1177/00223433030406004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Domestic and Foreign Pressure on Israeli Decisions To Use Limited Military Force

Abstract: The influence of domestic politics on international relations is a very popular theme in US foreign policy analysis. Numerous studies have demonstrated that presidents sometimes tried to improve their public ratings by adopting populist militant foreign policies. The question is whether such behavior is characteristic of democracies in general, or limited to the United States. While there is no reason to assume that in other democracies, or even non-democratic regimes, aggressive actions against a foreign thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…More specifically, social psychological studies have demonstrated that the key mediator of the rally effect is anger, and that public support for the leader will be enhanced if they are provoked regardless of their partisanship and ideology. The rally effect has also been a focal point for the study of nationalistic responses to external threats in international relations, ranging from economic sanctions to interstate conflict (Allen 2008;Drezner 1999Drezner , 2001Galtung 1967;Gibler 2010;Kuperman 2003;Lai and Reiter 2005;Marinov 2005;Mastanduno 1999).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, social psychological studies have demonstrated that the key mediator of the rally effect is anger, and that public support for the leader will be enhanced if they are provoked regardless of their partisanship and ideology. The rally effect has also been a focal point for the study of nationalistic responses to external threats in international relations, ranging from economic sanctions to interstate conflict (Allen 2008;Drezner 1999Drezner , 2001Galtung 1967;Gibler 2010;Kuperman 2003;Lai and Reiter 2005;Marinov 2005;Mastanduno 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these problems, Kuperman (2001b, 2003) adopted a multidimensional event history approach. This method, which is a derivation of a discrete‐time event history analysis (Allison 1982), is simply a logistic regression analysis predicting the probability of an event on a particular day as a function of various types of previous events and the amount of time that passes from each event type.…”
Section: Methodsmentioning
confidence: 99%
“…Although this could be resolved by measuring the association between the number of military initiatives and a temporal lag in time of the independent variables (Sprecher and DeRouen 2002), immediate responses within time periods that are shorter than the standard time units are excluded. This is especially relevant in the case of Israeli military initiatives, as there has always been a tendency to respond to Arab attacks as quickly as possible, within days or hours (Goldstein et al 2001; Kuperman 2001b, 2003:14–15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation